Silver-coated (Agluna®) tumour prostheses can be a protective factor against infection in high risk failure patients. Issue 4 (April 2019) - Parry, Michael C.; Laitinen, Minna K.; Albergo, Jose I.; Gaston, Czar L.; Stevenson, Jonathan D.; Grimer, Robert J.; Jeys, Lee M.
Abstract: Introduction: Endoprostheses in the treatment of extremity sarcomas are associated with late complications including periprosthetic infection. This study analysed the incidence of infection in patients undergoing endoprosthetic replacement (EPR) with a silver-coated prosthesis. Materials and methods: The study comprised a retrospective single centre study of 394 consecutive patients treated with resection and EPR for primary extremity bone tumours. Results: 89 patients at risk for infection were treated with a silver-coated (Agluna®) EPR (22.6%), compared to 305 patients treated with a non-silver EPR (77.4%). The incidence of periprosthetic infection, requiring revision as the primary endpoint was 34/394 (8.6%); 11 patients (12.4%) in the silver group and 23 patients (7.5%) in the non-silver group (p = 0.154). Overall implant survival was 90.9% and 95.3% at 1-year and 86.8% and 91.8% at 5-years in the silver-coated and non-silver coated group, respectively (p = 0.193). Infection was treated in the silver group by washout of the prosthesis in 2/11, debridement and implant retention (DAIR) in 1/11 and single-stage revision in 1/11, and in the non-silver group by washout in 1/23 or DAIR in 2/23. Two-stage revision was successful in 2/11in the silver group, and in 11/23 in the non-silver group. Amputation was required in 4/11 in the silver group and 9/23 in the non-silver group. One patient in the silver group died due to disease with an infected EPR. Conclusions: Silver-coated prostheses in high risk patients show similar infection free survival as non-silver coated prosthesis in standard sites in primary bone tumours of the extremities.